Stand‐alone intrathecal central nervous system (CNS) prophylaxis provide unclear benefit in reducing CNS relapse risk in elderly DLBCL patients treated with R‐CHOP and is associated increased infection‐related toxicity. (20th June 2019) - Eyre, Toby A.; Kirkwood, Amy A.; Wolf, Julia; Hildyard, Catherine; Mercer, Carolyn; Plaschkes, Hannah; Griffith, John; Fields, Paul; Gunawan, Arief; Oliver, Rebecca; Booth, Stephen; Martinez‐Calle, Nicolas; et al.
Summary: Central nervous system (CNS) relapse following R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisolone) occurs in 2–5% of patents with diffuse large B‐cell lymphoma (DLBCL). Many patients aged ≥70 years are unsuitable for high‐dose methotrexate (HDMTX) prophylaxis and therefore often receive stand‐alone intrathecal prophylaxis. The CNS international prognostic index (CNS‐IPI) is a clinical CNS relapse risk score that has not specifically been validated in elderly patients. The value of CNS prophylaxis in patients aged ≥70 years remains uncertain. Data on 690 consecutively R‐CHOP‐treated DLBCL patients aged ≥70 years were collected across 8 UK centres (2009–2018). CNS prophylaxis was administered per physician preference. Median age was 77·2 years and median follow‐up was 2·8 years. CNS‐IPI was 1–3 in 60·1%, 4 in 23·8%, 5 in 13·0% and 6 in 3·3%. Renal and/or adrenal (R/A) involvement occurred in 8·8%. Two‐year overall CNS relapse incidence was 2·6% and according to CNS‐IPI, 1–3:0·8%, 4:3·6%, 5:3·8% and 6:21·8%. Two‐year CNS relapse incidence for R/A was 10·0%. When excluding HDMTX ( n = 31) patients, there remained no change in unadjusted/adjusted CNS relapse for intrathecal prophylaxis effect according to CNS‐IPI. CNS‐IPI is valid in elderly R‐CHOP‐treated DLBCL patients, with the highest risk in those with CNS‐IPI 6 and R/A involvement. We observed no clear benefit for stand‐alone intrathecal prophylaxis but observed an independent increased risk of infection‐related admission during R‐CHOP when intrathecal prophylaxis was administered.